A multidimensional approach to evaluate the policy effectiveness of elite sport schools in Flanders - de Bosscher, V.; De Knop Sports, P. (Sport in Society: Cultures, Commerce, Media, Politics, 2016)
The increasing demands of elite sports make it difficult for talented young athletes to balance school and sport. This paper investigates the multi-dimensional policy effectiveness of elite sport schools (ESSs) in secondary education in Flanders. Four hundred and eight elite athletes who graduated from an ESS, and 341 from mainstream schools, completed an online survey. The data showed no clear evidence of more effective outputs (performance), or more positive evaluation of throughputs (processes) by athletes who attended an ESS. Athletes who did not attend an ESS received less support services, but those who did receive such services were generally more satisfied. They were equally satisfied about their coaches` expertise. Only training facilities were rated generally better in an ESS. The study concluded that evaluating effectiveness of ESS (at input-throughput-output level) requires a tailor-made, sport-specific approach. Furthermore, as ESS is only a small part of a total career, many other factors influence long-term success.